Management and Treatment Principles for Pediatric Abdominal and Thoracic Trauma After Disaster - Hakalmaz, Ali Ekber; Karagöz Hakalmaz, Ayşe; Topuzlu Tekant, Gonca (Cerrahpaşa Medical Journal, 2023)
Thoracoabdominal organ injuries are one of the most common causes of earthquake-related mortality in children. The majority of severe injuries are when caught under the rubbles. In severe cases who can reach health care in the early period, milder injuries, morbidity, and mortality can be prevented with effective and rapid interventions. In the management, physical examination and traditional diagnostic/therapeutic invasive methods become important as laboratory and imaging tools may be out of use in the early post-disaster period. On the other hand, it should always be kept in mind that Crush syndrome, which develops secondary to earthquakes, has more mortal outcomes. Therefore, interventions should be fast and effective. In addition to preventive approaches, learning medical intervention and adapting to unfavorable conditions in disaster situations is very important, especially for medical personnel of countries in seismic zone. Cite this article as: Hakalmaz AE, Karagöz Hakalmaz A, Topuzlu Tekant G. Management and treatment principles for pediatric abdominal and thoracic trauma after disaster. Cerrahpaşa Med J 2023;47(S1):83-88.